2022
DOI: 10.1038/s41598-022-14096-y
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effect of blue light on Asian tiger mosquito, Aedes albopictus (Diptera: Culicidae)

Abstract: In our previous studies, we found that blue light has a lethal effect on various insect species and demonstrated that the most effective wavelength to control the hygiene pest, the mosquito, Culex pipiens form molestus (Diptera: Culicidae), is ~ 420 nm through all developmental stages. The genera Aedes and Culex include many globally crucial hygiene pest species that transmit serious diseases to humans and animals. However, effective lethal wavelengths have been shown to differ among insect species. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The immediate avoidance of these environmental conditions is adaptive for longer periods because the mortality of the cocooned larvae is much higher under the sun (82.1% at maximum soil temperature ≥ 40.2 °C, full sunlight is 108,000 lx) than under the shade (4.5% at maximum soil temperature ≥ 29.9 °C) during the summer months of August and September 24 . Blue light is known to be lethal for insects 36 , 37 and this may be caused by the blue light enhancing the production of reactive oxygen species, such as in microbes and human cells 38 , 39 . Therefore, the avoidance of blue light directly reduces the lethal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate avoidance of these environmental conditions is adaptive for longer periods because the mortality of the cocooned larvae is much higher under the sun (82.1% at maximum soil temperature ≥ 40.2 °C, full sunlight is 108,000 lx) than under the shade (4.5% at maximum soil temperature ≥ 29.9 °C) during the summer months of August and September 24 . Blue light is known to be lethal for insects 36 , 37 and this may be caused by the blue light enhancing the production of reactive oxygen species, such as in microbes and human cells 38 , 39 . Therefore, the avoidance of blue light directly reduces the lethal effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that blue light exposure negatively affected the development, survival and reproductive fitness of S. frugiperda, with longer exposure resulting in harmful effects (Figures 1 and 2). Previous studies have shown that blue light irradiation can kill insects and that the lethal wavelengths of blue light are species-specific [6,7,16]. A few studies also demonstrated that blue light exposure negatively affected the T1H, T2H and T3H refer to female head from T1, T2 and T3 treatments, respectively; T1T, T2T and T3T refer to female thorax from T1, T2 and T3 treatments, respectively; T1A, T2A and T3A refer to female abdomen from T1, T2 and T3 treatments, respectively; CKH, CKT and CKA refer to control female head, thorax and abdomen, respectively; VS, versus.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that blue light exposure negatively affected the development, survival and reproductive fitness of S. frugiperda, with longer exposure resulting in harmful effects (Figures 1 and 2). Previous studies have shown that blue light irradiation can kill insects and that the lethal wavelengths of blue light are species-specific [6,7,16]. A few studies also demonstrated that blue light exposure negatively affected the reproduction of insects [53,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immediate avoidance of these environmental conditions is adaptive for longer periods because the mortality of the cocooned larvae is much higher under the sun (82.1% at maximum soil temperature ≥ 40.2°C, full sunlight is 108,000 lux) than under the shade (4.5% at maximum soil temperature ≥ 29.9°C) for two summer months; August and September 18 . Blue light is known to be lethal for insects 28,29 and this may be caused by the blue light enhancing the production of reactive oxygen species as in microbes and human cells 30,31 . Therefore, the avoidance of blue light directly reduces the lethal effect.…”
Section: Discussionmentioning
confidence: 99%